Feedback of Domestic Employers on the Household Servicing Competency of Kasambahays in Zamboanga Del Norte - Mansanadez, Evangeline; Aranda, Charo (JPAIR Multidisciplinary Research, 2019)
A healthy, safe and peaceful home where love and understanding abode is always the aim of every Filipino family.  This survey aimed to determine the feedback of domestic employers on the skill and competence of their Kasambahay along household servicing tasks such as cleaning, caring for the children, cooking, marketing and doing the laundry; the  use and maintenance of household materials and equipment; practice of occupational health and safety standards and relation towards employers and with others. A translated questionnaire-checklist was administered to 422 domestic employers in the 25 municipalities and 2 cities in the province of Zamboanga del Norte.  Findings led to the conclusion that the domestic employers find their Kasambahay to be skilled in household servicing tasks such as cleaning, caring for the children, cooking, marketing, and doing the laundry, competent on the use and maintenance of household materials and equipment and in practicing occupational health and safety standards. The domestic employers rated the attitude of their Kasambahay as satisfactory in the way the latter relate with others.
Keywords: domestic employers; household servicing tasks; use and maintenance of household materials and equipment; practice of occupational health and safety standards; relation towards employers; Philippines